2023
DOI: 10.3390/cells12091257
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Cd44 Inhibits Metastasis Formation of Liver Cancer in Nf2-Mutant Mice

Abstract: Primary liver cancer is the third leading cause of cancer-related death worldwide. An increasing body of evidence suggests that the Hippo tumor suppressor pathway plays a critical role in restricting cell proliferation and determining cell fate during physiological and pathological processes in the liver. Merlin (Moesin-Ezrin-Radixin-like protein) encoded by the NF2 (neurofibromatosis type 2) gene is an upstream regulator of the Hippo signaling pathway. Targeting of Merlin to the plasma membrane seems to be cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Accordingly the upregulation of CD44 is observed in HFD diet fed animals displaying inflammation, fibrosis and is particularly significantly associated with the malignant transformation of hepatocytes in NAFLD 52 53 . The deletion of CD44 inhibits metastasis formation in mice 54 and in obese patients, hepatic CD44 and serum sCD44 strongly correlated with NASH 55 . Indeed, CD44 is considered a cancer stem cell marker 56 where immunohistochemical analysis of human HCC samples demonstrate increased expression of CD44.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly the upregulation of CD44 is observed in HFD diet fed animals displaying inflammation, fibrosis and is particularly significantly associated with the malignant transformation of hepatocytes in NAFLD 52 53 . The deletion of CD44 inhibits metastasis formation in mice 54 and in obese patients, hepatic CD44 and serum sCD44 strongly correlated with NASH 55 . Indeed, CD44 is considered a cancer stem cell marker 56 where immunohistochemical analysis of human HCC samples demonstrate increased expression of CD44.…”
Section: Discussionmentioning
confidence: 95%
“…Ho et al identified a CD24/CD44-enriched cell subpopulation within EpCAM cells through single-cell transcriptomics, indicating a novel stemness-related cell subclone in HCC ( Ho et al, 2019 ). Deletion of CD44 significantly inhibited metastasis formation of HCC in Nf2-mutant mice ( Gerardo-Ramirez et al, 2023 ). Furthermore, the importance of SOX9 in HCC prognosis has been verified in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly the upregulation of CD44 is observed in HFD diet fed animals displaying inflammation, fibrosis and is particularly significantly associated with the malignant transformation of hepatocytes in NAFLD 47 48 . The deletion of CD44 inhibits metastasis formation in mice 49 and in obese patients, hepatic CD44 and serum sCD44 strongly correlated with NASH 50 . Indeed, CD44 is considered a cancer stem cell marker 51 where immunohistochemical analysis of human HCC samples demonstrate increased expression of CD44.…”
Section: Fibrosis and Hccmentioning
confidence: 95%